1986
DOI: 10.1073/pnas.83.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of splicing but not cleavage at the 5' splice site by truncating human beta-globin pre-mRNA.

Abstract: Human P-globin mRNAs truncated in the second exon or in the first intron have been processed in vitro in a HeLa cell nuclear extract. Transcripts containing a fragment of the second exon as short as 53 nucleotides are efficiently spliced, whereas transcripts truncated 24 or 14 nucleotides downstream from the 3' splice site are spliced inefficiently, if at all. AU of these transcripts, however, are efficiently and accurately cleaved at the 5' splice site. In contrast, RNA truncated in the first intron, 54 nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
(44 reference statements)
2
22
1
Order By: Relevance
“…We have shown previously that efficient removal of intron 1 of the human ,B-globin premRNA can be dramatically reduced in vitro by truncating the transcript so that only 14 nucleotides of the second exon remain. This transcript is able to undergo the first step in splicing, i.e., cleavage at the 5' splice site and lariat formation, but is unable to efficiently generate the final spliced product or the released lariat intron (7). Similar observations have also been reported by Ruskin and Green (24).…”
supporting
confidence: 74%
“…We have shown previously that efficient removal of intron 1 of the human ,B-globin premRNA can be dramatically reduced in vitro by truncating the transcript so that only 14 nucleotides of the second exon remain. This transcript is able to undergo the first step in splicing, i.e., cleavage at the 5' splice site and lariat formation, but is unable to efficiently generate the final spliced product or the released lariat intron (7). Similar observations have also been reported by Ruskin and Green (24).…”
supporting
confidence: 74%
“…This hypothesis cannot be rejected in the case of the mismatched introns in the o~(IV) and ce2(IV) genes. Actually, it has been shown that at least in the fl-globin gene exons smaller than 24 if at all [44]. This finding cannot be generalized, however, as an 11 bp long exon containing a part of the sequence coding for the signal peptide cleavage site has been identified in the chicken procr2(I) collagen gene [45].…”
Section: Discussionmentioning
confidence: 65%
“…Although it has been known that both the sequences (6,12,14,35,41,49,51) and the lengths (2,9,13,14,34,44,48,51) of exons are important determinants in the mechanism of splice site selection, the details of their involvement are not well understood. We have presented here a method for probing exon sequences with 2'-O-methyl oligoribonucleotides in search of the signals required for splice site selection.…”
Section: Methodsmentioning
confidence: 99%